Deferiprone, an iron chelator, alleviates platelet hyperactivity in patients with β-thalassaemia/HbE - Ngan Thi Tran; Pranee Sutcharitchan; Jindaporn Janprasit; Ponlapat Rojnuckarin; Noppawan Phumala Morales; Rataya Luechapudiporn (BioExcel Publishing Ltd, 2022)
Background: Hyperfunctional platelets play important roles in thromboembolism in patients with β-thalassaemia/ haemoglobin E (β-thal/HbE). Our previous study revealed ex vivo inhibitory effects of deferiprone on normal platelets. Herein, we aimed to investigate the in vivo effects on platelets in patients with β-thal/HbE. Methods: A prospective, self-controlled clinical study on 30 patients with β-thal/HbE who had received therapeutic deferiprone (20.8-94.5 mg/kg/day) was conducted. The study included a 4-week washout period followed by 4 and 12 weeks of deferiprone treatment. Platelet aggregation was performed by a turbidimetric method. Levels of deferiprone and soluble platelet (sP)-selectin in serum were measured by high-performance liquid chromatography (HPLC) and enzyme-linked immunosorbent assay (ELISA) kit, respectively. Results: The washout period significantly enhanced platelet hyperactivity both in patients who had undergone splenectomy and in those who had not. At 2 hours following the administration of a single dose of deferiprone, platelet sensitivity to ADP and arachidonic acid was significantly reduced. The inhibitory effects of deferiprone were gradually increased over the period of 4 and 12 weeks. Deferiprone also depressed sP-selectin levels, but the effect was stable over longer follow-up periods. Correlation analysis demonstrated the relationship between serum levels of deferiprone, sP-selectin, and platelet activities induced by ADP and arachidonic acid. Conclusion: We first demonstrated the in vivo antiplatelet effect and benefit of short-term treatment of deferiprone in patients with β-thal/HbE. The impact on thrombotic outcomes deserves further study.